Can scenic indicator help sustaining healthy ecosystems of Fraser’s Hill? - Othman, Jamilah; K. A., Nur Emira; R. A. R., Nur Fatin (WIT Press, 2015)
Ecological landscape is among the factors that may implicate tourists’ visitations to a nature-based landscape of highland environment. It is found that the natural beauty of certain natural resources has a significant contribution to the development of a nature-based tourism. Perhaps, sustainable landscape management is essential to continuously maintain the rich biodiversity of an ecosystem. This study assessed the correlation of scenic beauty of Fraser’s Hill to its ecological landscapes. The natural heritage of Fraser’s hill can be identified through its unique ecosystems (e.g. forest, waterfall and lake) that house varieties of flora and fauna. This study had adopted the perception-based paradigm, in which the public were the respondents. The necessary data were collected using: 1) photographic questionnaire survey (non-locals public) and 2) questionnaire survey (in situ tourists). Earlier, an exploratory field observation (EFO) was carried out on site to determine the potential ecological attributes. Results of the questionnaire survey show that the ecological attributes (e.g. hilly landform, greenery and water elements) have implicated the scenic beauty of Fraser’s Hill. Similarly, the results obtained from the second instrument agree that the ecosystems (e.g. lake and waterfall) with ecological attributes are most preferred for. Findings show that there is high agreement on the scenic beauty of the natural and historical heritage. The insights provide quantitative information that may implicate the sustainability of highland environment, highland management practices, local authorities, economic value, tourism industry and many more. Importantly, the findings suggest that scenic beauty can be an indicator to healthy ecosystems that may further sustain other sensitive environments of Malaysia.